Chitosan based controlled release drug delivery of mycophenolate mofetil loaded in nanocarriers system: synthesis and in-vitro evaluation. (4th March 2021) - Zaman, Muhammad; Iqbal, Asma; Haider Rizvi, Syed Farhan; Hussain, Muhammad Ajaz; Jamshaid, Talha; Jamshaid, Muhammad
Abstract: Background: Organ transplantation is an important and critical procedure, which requires the suppression of immunity, and to suppress the immunity, a constant plasma concentration of immunosuppressant is required. Objectives: The said objective can be achieved by formulating a controlled release drug delivery system of the drug. Chitosan (CHT) nanoparticles (NPs) have been revolutionizing the conventional drug delivery system, for the past two decades. The aim of the current research work was to develop and evaluate CHT-based mycophenolate mofetil (MMF) loaded nanoparticles (CHT/MMF-NPs) using different drug to polymer ratios. Methods: The challenge was to entrap a lipophilic drug within NPs by the ionic gelation method of the positively charged CHT, using tripolyphosphate (TPP) as the crosslinking agent. The prepared CHT/MMF-NPs were evaluated for physical and chemical characterizations, including particle size, surface charge, entrapment efficiency (EE), surface morphology by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) for chemical compatibilities, X-ray diffractometry (XRD) and in-vitro dissolution studies. Results: Outcomes of the studies revealed that particles were 260 ± 17 nm in diameter, with the smooth and regular surface. Satisfactory values of EE (99%) have indicated the suitability of selected ingredients and employed methodology. Moreover, FTIR has confirmed the chemical compatibilities of the formulations. In-vitro dissolution studies have indicated diffusion type of controlled and sustained drug release during 24 h, with zero-order, as best fit kinetic model. Conclusion: Conclusively, the successful achievement of objectives has indicated the suitability of excipients and methodology to prepare CHT/MMF-NPs for better therapeutic outcomes.